Safety and pharmacodynamics of venetoclax (ABT-199) in a randomized single and multiple ascending dose study in women with systemic lupus erythematosus. (February 2018) - Lu, P; Fleischmann, R; Curtis, C; Ignatenko, S; Clarke, S H; Desai, M; Wong, S L; Grebe, K M; Black, K; Zeng, J; Stolzenbach, J; Medema, J K
Objective: The anti-apoptotic protein B-cell lymphoma 2 (Bcl-2) may contribute to the pathogenesis of systemic lupus erythematosus. The safety, tolerability, and pharmacodynamics of the selective Bcl-2 inhibitor venetoclax (ABT-199) were assessed in women with systemic lupus erythematosus. Methods: A phase 1, double-blind, randomized, placebo controlled study evaluated single ascending doses (10, 30, 90, 180, 300, and 500 mg) and multiple ascending doses (2 cycles; 30, 60, 120, 240, 400, and 600 mg for 1 week, and then 3 weeks off per cycle) of orally administered venetoclax. Eligible participants were aged 18–65 years with a diagnosis of systemic lupus erythematosus for 6 months or more receiving stable therapy for systemic lupus erythematosus (which could have included corticosteroids and/or stable antimalarials). Results: All patients (48/48) completed the single ascending dose, 25 continued into the multiple ascending dose, and 44/50 completed the multiple ascending dose; two of the withdrawals (venetoclax 60 mg and 600 mg cohorts) were due to adverse events. Adverse event incidences were slightly higher in the venetoclax groups compared with the placebo groups, with no dose dependence. There were no serious adverse events with venetoclax. The most common adverse events were headache, nausea, and fatigue. Venetoclax 600 mg multiple ascending dose treatment depleted total lymphocytes and B cells by approximately 50% and 80%, respectively. Naive, switched memory, and memory B-cell subsets enriched in autoreactive B cells exhibited dose-dependent reduction of up to approximately 80%. There were no consistent or marked changes in neutrophils, natural killer cells, hemoglobin, or platelets. Conclusions: Venetoclax was generally well tolerated in women with systemic lupus erythematosus and reduced total lymphocytes and disease-relevant subsets of antigen-experienced B cells. Registration: ClinicalTrials.gov: NCT01686555.